Mathematical modelling of hypoglycaemia and lactic acidosis in the bloodstream of Plasmodium berghei infected rats: a feasibility study - Walters, Nicolas (Stellenbosch : Stellenbosch University, 2016)
Thesis (MSc)--Stellenbosch University, 2016